Neural stem cells fate under neuroinflammatory conditions and oxidative stress response - Torrisi, Filippo; Denaro, Simona; Ragonese, Jenny; D’Aprile, Simona; Zappalà, Agata; Parenti, Rosalba (Frontiers in Cellular Neuroscience, 2025)
Neural stem cells (NSCs) are defined by their self-renewal capacity and multipotent differentiation potential, making them essential for nervous system development and for the maintenance of adult brain homeostasis. Although confined to the subventricular zone and the subgranular zone of the hippocampus in adulthood, NSCs preserve a functional capacity for neurogenesis and tissue regeneration. This regenerative potential becomes particularly important in neuropathological conditions, where tissue damage is often accompanied by neuroinflammation and oxidative stress. Within this hostile microenvironment, NSCs have to cope with inflammatory mediators and reactive oxygen species that can affect their survival, proliferation, and cellular differentiation. NSCs also are actively modulated by diverse molecular pathways in response to stress conditions promoting stemness or stem cell exhaustion. Therefore, understanding the crosstalk between neuroinflammatory and oxidative stress in NSCs fate is crucial for elucidating the mechanisms of neurogenesis and homeostasis recovery and for designing therapeutic strategies.